Accounts that count: Rural Producers in Spaces Intended to Nature Conservation - Torres, Laura María (2020)
We analyze the presence of rural producers dedicated to livestock inside and in the borders of lands intended for nature conservation. In Mendoza— an interior province of Argentina—the integration of disperse secondary data allows to describe the evolution of spaces meant for the conservation and to analyze the overlapping of protected areas and territories that support domestic units of rural production dedicated to extensive livestock. Results show that almost 40% of domestic rural units of Mendoza are located inside or in the borders of territories under conservation regulations and that overlapping has increased during the last years concurring with the expansion of the protected lands and the deepening of neoliberalism. The characterization of productive activities developed by rural communities and their use of space and nature ultimately allow to identify grey zones regarding our knowledge of the present, and also to assess main subjects that may encompass the study of social-ecological diversities associated with protected spaces. We expect to enable social-ecological readings of the social structures characteristic of spaces meant for conservation, and also to contribute with references for future diachronic and comparative works that may study the processes of displacement for conservation.